INCREASING SCHOOL EFFECTIVENESS THROUGH PRINCIPALS’ LEADERSHIP AND TEACHERS’ TEACHING PERFORMANCE, IS IT POSSIBLE? - Heni Mulyani; Danny Meirawan; Annisa Rahmadani (Jurnal Cakrawala Pendidikan, 2020)
Efforts to achieve educational goals can’t be separated from the performance of schools in realizing these goals, to achieve this involves many parties and factors that influence it. This study aims to describe the impact of principal’s leadership and teacher’s teaching performance in an effort to increase school effectiveness. This research uses a quantitative approach with a survey method. Population are 466 schools, samples of 210 schools were taken by proportionated stratified random sampling technique, and a total of 2,730 respondents consisted of principals, teachers, students, and school committees. The instrument used was a questionnaire, data processing techniques using the Structural Equation Model. The results indicate that principals’ leadership and teachers’ teaching performance positively and significantly influence school effectiveness, which means that school effectiveness directly determined by the presence of effective principal’s leadership and high teacher teaching performance. The principal's leadership as a driver variable is proven to be able to trigger the teaching performance of teachers to increase school effectiveness. The high effectiveness of this school is inseparable from the effective teacher’s teaching performance. Teachers' teaching performance must be continuously improved to improve school effectiveness. This teaching performance can be improved through the principal's leadership role.